Sodium hexafluorophosphate mediated enhancement of electrical and electrochemical properties of poly(vinyl alcohol)-chitosan solid polymer electrolytes for EDLCs - Cyriac, Vipin; Ismayil; Mishra, Kuldeep; Rao, Ankitha; Khellouf, Riyadh Abdekadir; Masti, Saraswati P.; Noor, I. M. (Royal Society of Chemistry, 2025)
A free-standing, flexible and biodegradable biopolymer electrolyte (BPE) derived from a poly(vinyl alcohol) (PVA)-chitosan (CS) blend immobilizing sodium hexafluorophosphate (NaPF6) salt was fabricated via solution casting method. The effect of salt concentration on the structural, electrical, and electrochemical properties of the electrolyte was systematically investigated. X-ray diffraction (XRD) and Fourier-transform infrared (FTIR) spectroscopy were used to ascertain the microstructural changes in the polymer matrix including the complexation of PVA, CS, and NaPF6. Electrochemical impedance spectroscopy (EIS) measurements revealed that the BPE containing 40 wt% NaPF6 exhibited the highest conductivity (6.94 ± 0.04) × 10−5 S cm−1, which was three-order enhancement over the pristine system. The ion transport behaviour, interpreted through the Schütt and Gerdes (S-G) model, revealed that the ionic conductivity of the SPE system is strongly influenced by both the concentration of charge carriers and their mobility. The electrolyte displayed a predominant ionic nature with an electrochemical stability window of ∼3.25 V. When incorporated into an Na-ion EDLC, the optimized electrolyte sample provided a specific capacitance of 42.65 F g−1, energy density of 5.4 W h kg−1, and power density of 95 W kg−1, as determined by galvanostatic charge-discharge (GCD) tests performed at 0.05 mA g−1